EXPLORATORY FACTOR STRUCTURE OF PROFESSIONAL TRAINING EXPECTATIONS - García Lirios, Cruz (Hitos de Ciencias Económico Administrativas, 2020)
OBJECTIVE: The main objective of this wok is the exploration of two preponderant dimensions of professional training. MATERIAL AND METHOD: An experimental study was carried out with a non-probabilistic selection of 300 students, considering their insertion in professional practices and social service in organizations allied with the public university. RESULTS: A dual structure of norms and values found with eight indicators explain the formation of job expectations in future professionals. CONCLUSION: The design limited the findings to the research scenario, suggesting the inclusion of other factors as well as the comparison of the model in other vocational training contexts such as the companies that participate in government subsidies to promote the first job in young graduates.